2010
DOI: 10.1017/s0033291710001777
|View full text |Cite
|
Sign up to set email alerts
|

The association of personality disorders with the prospective 7-year course of anxiety disorders

Abstract: Background This study prospectively examined the natural clinical course of six anxiety disorders over 7 years of follow-up in individuals with personality disorders (PDs) and/or major depressive disorder. Rates of remission, relapse, new episode onset and chronicity of anxiety disorders were examined for specific associations with PDs. Method Participants were 499 patients with anxiety disorders in the Collaborative Longitudinal Personality Disorders Study, who were assessed with structured interviews for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 37 publications
5
89
0
Order By: Relevance
“…While imperfect and prone to bias, formulating a picture of temporal relationships between drinking and personality functioning is a cornerstone of treating this challenging group. Some have hypothesized that PD is better considered a diathesis [38-40] or cause of recurrence [41] as opposed to a separate disorder. Irrespectively of how the problems of personality or alcoholism are conceptualized, a coherent nosological approach [42] and formulation provide a clear clinical pathway forward from which the literature can be applied.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…While imperfect and prone to bias, formulating a picture of temporal relationships between drinking and personality functioning is a cornerstone of treating this challenging group. Some have hypothesized that PD is better considered a diathesis [38-40] or cause of recurrence [41] as opposed to a separate disorder. Irrespectively of how the problems of personality or alcoholism are conceptualized, a coherent nosological approach [42] and formulation provide a clear clinical pathway forward from which the literature can be applied.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…The association may be understood in part with reference to broader literature concerning personality disorder, anxiety and depression, as well as other work showing that personality disorder is a risk factor for poor future mental health (Moran et al, 2016). High comorbidities between personality disorder and anxiety (Friborg et al, 2013) and depression (Friborg et al, 2014) are well documented, and coexisting personality disorder has been linked to poorer outcomes in anxiety (Ansell et al, 2011) and depression (Grilo et al, 2010). Our finding of an attenuated association between personality disorder and antenatal depressive symptoms with the adjustment for preconception background factors including common mental disorder does not negate the possibility of an independent association between personality disorder and antenatal depression.…”
Section: Discussionmentioning
confidence: 99%
“…They are associated with functional impairments that can persist even when diagnostic thresholds are no longer met (Skodol et al, 2005) and are linked to premature mortality (Fok et al, 2012). Rates of comorbid anxiety (Friborg et al, 2013) and depression (Friborg et al, 2014) are high in personality disorder, and comorbid personality disorder predicts poorer outcomes for these disorders (Ansell et al, 2011;Newton-Howes et al, 2014). Furthermore, our group has recently shown that the presence of personality disorder in young adulthood independently predicts future anxiety and depression over a decade later (Moran et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…Variables known to be associated with DSM diagnoses such as dispositional traits, for example negative affect, submissiveness, low affect tolerance, and introversion, are ignored in most studies; as are additional confounds such as levels of distress and impairment, co-occurring problems, history of adversity, level of self-reflectiveness, tolerance for emotion, and access to social supports (Cain, Ansell, Wright, Hopwood, & Thomas, 2012;Krueger, 2002). We do not adequately understand how these moderators interact with and impact on the effectiveness of different therapeutic approaches, but there is substantial evidence available that each can impact outcome (Ansell, Pinto, Edelen, Markowitz, Sanislow, Yen et al, 2011;Beutler, Malik, Alimohamed, Harwood, Talbi, Noble et al, 2004;Norcross & Wampold, 2011;Westen & Morrison, 2001;Zanarini, Frankenurg, Reich, & Fitzmaurice, 2012;Zanarini, Horz, Frankenburg, Weingeroff, Reich, & Fitzmaurice, 2011).…”
Section: Sampling Practicesmentioning
confidence: 99%